2020
DOI: 10.1108/wjemsd-07-2019-0060
|View full text |Cite
|
Sign up to set email alerts
|

Youth employment in Ghana: economic and social development policies perspective

Abstract: PurposeCreating employment opportunities for the youth remains a dilemma for policymakers. In many cases, policies and programmes to tackle youth unemployment have produced little results, because such initiatives have failed to consider some fundamental inputs. In Ghana, youth unemployment rate has doubled or more than doubled the national average unemployment rate in recent years. The current study, therefore, examines how policies in the past two decades have affected youth unemployment rate and other devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The key area of interest explored could be factors influencing youth unemployment such as duration dependence (Flek et al , 2015; Cockx and Picchio, 2013; Raaum, 2009; García-Pérez and Muñoz-Bullón, 2005), skills (Cyron and Mehrotra, 2022; Groh et al , 2016), training (Šileika, 2004; Upward, 2002), income distribution (De Fraja et al , 2021; Singh et al , 2020), labour market (Liotti, 2022; Ylistö and Husu, 2021; Ranchhod and Daniels, 2021; Bradley and Crouchley, 2020), policies (Jumpah, 2020; Focacci, 2020), wage determination (Gabriel and Schmitz, 2020; Vasilescu and Begu, 2019), minimum wage (Fialová and Mysíková, 2021; Marimpi and Koning, 2018), labour supply (Holford, 2020; McTier and McGregor, 2018), education (Cyron and Mehrotra, 2022; Juárez et al , 2022; Krahn et al , 2015; Odoardi, 2020; Pompei and Selezneva, 2021; Meyer and Mncayi, 2021) and youth entrepreneurship (Munyuki and Jonah, 2021; Justina and Emmanuel, 2020; Jumpah, 2020; Ubogu, 2020).…”
Section: Results and Findingsmentioning
confidence: 99%
“…The key area of interest explored could be factors influencing youth unemployment such as duration dependence (Flek et al , 2015; Cockx and Picchio, 2013; Raaum, 2009; García-Pérez and Muñoz-Bullón, 2005), skills (Cyron and Mehrotra, 2022; Groh et al , 2016), training (Šileika, 2004; Upward, 2002), income distribution (De Fraja et al , 2021; Singh et al , 2020), labour market (Liotti, 2022; Ylistö and Husu, 2021; Ranchhod and Daniels, 2021; Bradley and Crouchley, 2020), policies (Jumpah, 2020; Focacci, 2020), wage determination (Gabriel and Schmitz, 2020; Vasilescu and Begu, 2019), minimum wage (Fialová and Mysíková, 2021; Marimpi and Koning, 2018), labour supply (Holford, 2020; McTier and McGregor, 2018), education (Cyron and Mehrotra, 2022; Juárez et al , 2022; Krahn et al , 2015; Odoardi, 2020; Pompei and Selezneva, 2021; Meyer and Mncayi, 2021) and youth entrepreneurship (Munyuki and Jonah, 2021; Justina and Emmanuel, 2020; Jumpah, 2020; Ubogu, 2020).…”
Section: Results and Findingsmentioning
confidence: 99%
“…First, unemployment in youth is a primary concern for India. It creates emotional, mental, and financial insecurities among youth [ 49 , 50 ]. Several studies have concluded that unemployment leads to anxiety, stress, depression, and psychological trauma.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, the remarkable drop in the absolute number of formal workers in the Ghanaian economy has been a source of controversy and public concern. The long-term employment relationship is an important feature of many developing countries as an estimated 30% to 70% of the labour force in developing countries is employed in informal jobs (Bosch & Esteban-Pretel, 2012;Jumpah et al, 2020). As indicated by Liu (2018), the dynamics of the labour market are associated with the creation of new jobs and the destruction of old ones at the firm level.…”
Section: Introductionmentioning
confidence: 99%